Bioprotective Role of Lactic Acid Bacteria in Food Preservation with Emphasis on Industrial Applications and Commercial Prospects: Article Review - D, Mohammed.; M.Shekhani, Dawod Noori (American Journal of Biology and Natural Sciences, 2025)
This review discusses lactic acid bacteria (LAB) as bio-protectors vs. chemical preservatives, focusing on the mechanisms of action along with the industrial applications, and regulatory-economic aspects. First, LAB produce acid and bacteriocins that inhibit pathogenic bacteria and fungi, and thus prevent spoilage and prolong shelf life without negatively changing flavor and texture. Second, it describes the practical application in dairy, meat, plant-based products and active bio-packaging in the reduction of salt, nitrite, and synthetic additives. Thirdly, this review discusses the technological aspects (i.e., sublethal stress conditioning, drying procedure, microencapsulation) of LAB performance, and concludes by presenting means to improve the stability of cells and to reduce costs. Regulatory and safety considerations are also discussed, validating LAB as GRAS/QPS and bacteriocin usage limits. Lastly, the paper discusses business opportunities, expected market growth rates, and upcoming challenges, including targeting spore-forming pathogens, optimizing “omics” tools, and generating highly-efficient genetically engineered strains. The paper ends with an appeal for stronger co-operation between researchers, industry and regulators to drive strain performance, process optimisation and regulatory modernisation, which will in turn promote the adoption of sector-wide sustainable biopreservation in food supply chains worldwide.